Collection behaviour of lightweight packaging waste by individual households and implications for the analysis of collection schemes. (15th April 2019) - Thoden van Velzen, E.U.; Brouwer, M.T.; Feil, A.
Highlights: Separate collection of 21 households has been explored for 48 types of packaging. Performance indicators were proposed for separate collection schemes. Participation rates vary between collection methods and municipalities. Selection rates of participating civilians for plastic packages are fairly constant. Abstract: The separate collection behaviour of 21 Dutch households was explored. Their lightweight packaging waste (LWP) and mixed municipal solid waste (MSW) was studied twice in detail. The derived net collection yields for plastic packages and beverage cartons were high (mostly between 80 and 100%). A detailed analysis revealed that several packaging types were almost completely separate collected by these households. This observation led to the hypothesis that several packaging types will always be completely separate collected by participating civilians. Five indicator items were chosen and their concentrations in mixed MSW and LWP were used to calculate the minimal participation rate (PRmin ) for collection areas. This PRmin is an underestimation of the true participation rate since the population within a collection area will also contain non-ideal separating individuals. Analysis of 15 different municipalities with this new methodology revealed that the PRmin varied strongly from roughly 30% for a municipality with a drop-off collection scheme for only plastic packaging and no PAYT financial trigger to almost 90% for municipalities with a kerbside collection scheme for LWP and a PAYT financial trigger. Surprisingly, participating civilians in all collection schemes kept roughly the same share of desired plastic packages (DPP) separate (73 ± 11%) in all collection schemes. This share is derived from the PRmin and hence a slight over-estimation. The latter was named the maximum selection rate for desired plastic packages (SRmax DPP ). The PRmin and SRmax DPP form the basis of a new set of technical performance indicators for separate collection schemes of LWP.